Role of miRNAs in Cancer Analysis of Their Targetome - Navarro, Alfons (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
MicroRNAs are the best representatives of the non-coding part of the genome and their functions are mostly linked to their target genes. During the process of carcinogenesis, both dysregulation of microRNAs and their target genes can explain the development of the disease. However, most of the target genes of microRNAs have not yet been elucidated. In this book, we add new information related to the functions of microRNAs in various tumors and their associated targetome.